Analysis of Motor Vehicle Taxpayer Compliance at UPTD-PPD SAMSAT Tomohon - DIDIPU, Annisa; WARONGAN, Jessy; MINTALANGI, Syermi (Journal of Governance, Taxation and Auditing, 2023)
Tax is mandatory contribution of the people to the state that is coercive and cannot be directly rewarded for services. Taxes serve as a source of funds for the government to finance its expenses. Tax compliance is one of the supports that can increase local original revenue. The purpose of this study is to determine the compliance of motor vehicle taxpayers in UPTD-PPD SAMSAT Tomohon. This study used qualitative research methods. Data collection was carried out through direct field observation. The resulta showed that in fulfilling their tax obligations, taxpayers must meet the specified conditions, namely understanding the provisions of motor vehicle tax laws and regulations, filling out forms completely and clearly, calculating taxes owed correctly, paying taxes owed on time, not having tax arrears, never being convicted of committing criminal acts in the field of taxation. However, in carrying out its tax obligations, there are factors that affect taxpayer compliance including taxpayer awareness, econokic factors, bust work and service quality. To improve taxpayer compliance, the government has made various efforts including innovating and improving the administrative system, adding service advertisements and socializing programs to build public awareness.